The Reception of Learned Law in Fourteenth- and Fifteenth-Century Frisia - Wiegand, Marvin, (Late Antiquity and Medieval Studies E-Books Online, Collection 2024., 2025)
This book offers the first comprehensive analysis of medieval Frisian law, focusing on the influence of Roman and canon law in the fourteenth and fifteenth centuries. It makes use of recent translations of Old Frisian legal texts to show the evolution of Frisian law and to unveil why the Frisians were motivated to change their traditional laws. The book covers everything from oaths as evidence in Frisian procedures, to whether Frisian widows could be guardians of their children, to the role the Frisians themselves played in the evolution of their legal system. See Less